ANALISIS YURIDIS KEBIJAKAN PEMERINTAH TENTANG PENYEDIAAN FASILITAS KHUSUS MENYUSUI DAN/ATAU MEMERAH ASI UNTUK MENDUKUNG PROGRAM ASI EKSLUSIF DI PROVINSI LAMPUNG - Okta Ainita (Law Faculty of Universitas Bandar Lampung, 2019)
ABSTRACT Breastmilk, which is called as Exclusive Breastmilk is given to baby since the day baby is born until 6 (six) months without adding and / or replacing with other foods or beverages. Governments are responsible for setting policy in order to guarantee the right of infants and children to get the exclusive breastmilk. Regulatory Policy Regions in Lampung Province related to exclusive breastfeeding is still less effective. Coverage of babies who get exclusive breastfeeding in Lampung Province in 2015 is amounted to 57.70%, which is still below the figure from the expected target as 80%. The Government policy on provision of special breastfeeding facilities in the workplace and public facilities for its implementation has not been fully implemented in accordance with the provisions prevailing laws and regulations. Particularly in the Province of Lampung, based on the observation of researchers, there is an office providing nursery room, but the standard is not good enough and also the facilities in it are not yet eligible. In line with that, the nursery room which exist in public places like terminal, shopping center, tourist attractions, hotels still do not provide specific facilities for breastfeeding activity. The law enforcement against the disfunction of working places and public places which do not provide nursery room like private sector, government offices, regional government as well is still going on. As the conclusion, the lack of opportunity given by the respective institutions still reflect that breastfeeding mothers still have no proper opportunity to deliver their rights in using the facilities. It also could be said that the regulation has not been running the way it should be regarding the existing regulations.